INOVASI TUNNEL FISH DRYER BERBASIS KEARIFAN LOKAL â€œBAKAR BATUâ€ SEBAGAI CADANGAN PANAS - Pither Y. Boimau; Daniel Herison Wadu; Magda Y. Laka; Alo Liliweri (Jurnal Teknologi Perikanan dan Kelautan, 2021)
The implementation of a cheap and appropriate technology is needed for further handling process of fishermen products, in which the products can be stored for a longer time in the form of dried/smoked fish. The study objective was to implement a cabinet model fish dryer (Tunnel Fish Dryer) to improve the quality of dried fish by using andesite stone as a heat storage, which was placed on fire as a heating material. The heat was flowing into the fish heating room through the pipe using a fan. The five levels drying time frame period could produce the best quality smoked fish using a Completely Randomized Design (CRD). Each time frame had a different duration with three time repetitions, resulting in 15 experimental unit results. The drying times were as follows: A = 3 hours; B = 3.5 hours; C = 4 hours; D = 4.5 hours; and E = 5 hours. The results showed that the best drying time for dried fish was at 4.5 hours.